Cultural Hybridity and Identity Crisis in The Inheritance of Loss - M. E. Tennyson (Studies in Social Science & Humanities, 2024)
This paper explores the themes of cultural hybridity and identity crisis in Kiran Desai’s novel, The Inheritance of Loss. Set in post-colonial India and the United States, the novel delves into the lives of characters who navigate the complexities of hybrid identities and the resulting psychological turmoil. Through a detailed analysis of characters such as Sai, Jemubhai Patel, and Biju, the study examines how colonial legacies and global influences shape their fragmented identities. The socio-political backdrop of the Gorkhaland movement further enriches the narrative, highlighting the interconnectedness of individual and collective struggles for recognition and self-definition. This paper underscores the importance of understanding the multifaceted nature of identity in a globalized world and the ongoing impact of colonial histories on contemporary identities.